Assessing Feasibility of Using Quality of Life Questionnaire in Head and Neck Cancer Patients Undergoing Palliative Radiation Therapy - Velarasan, Kanmani; Ramasundaram, Deivanayagam (Asian Pacific Journal of Cancer Care, 2022)
Objective: Advanced head and neck cancer patients have distressing symptoms and bad prognosis. They have very limited treatment options. Radiation therapy in palliative intent appears to decrease symptoms. But there are limited data on palliative radiation therapy in relation to quality of life. Materials and methods: We conducted a pilot study to assess the feasibility of using quality of life questionnaire in patients undergoing palliative radiation therapy. Advanced head and neck cancer patients who are deemed incurable were recruited. Results: Out of 15 patients, 9 were males and 6 were females. 6 patients were in 51-60 years age group followed by 3 patients in 61-70 years age group. Significant improvement was seen in the physical domain at the end of radiotherapy course. Only 8 patients completed the questionnaire at 4, 8 and 12 weeks. 5 patients skipped the scheduled follow ups occassionally. Conclusion: There is a urgent need to devise a simple and validated tool for prognostication and to improve the quality of life. Intent of treating these patients should be according to patient directed goal of care.